2001
DOI: 10.1111/j.1346-8138.2001.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

Bullous Lichen Planus Arising in the Skin Graft Donor Site of a Psoriatic Patient

Abstract: The coexistence of psoriasis vulgaris and bullous disorders, particularly bullous pemphigoid, has been described previously. We present an unusual case of bullous lichen planus arising in the skin graft donor site of a psoriatic patient. To our knowledge, such an association has not been reported to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 14 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…[ 2 ] Few reports have highlighted the association of oral, linear, or bullous LP with psoriasis in adults. [ 6 7 8 ] A literature review revealed only two case reports with this association in children. [ 3 4 ] Both children had concurrent vitiligo over which subsequently psoriasis and LP developed.…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Few reports have highlighted the association of oral, linear, or bullous LP with psoriasis in adults. [ 6 7 8 ] A literature review revealed only two case reports with this association in children. [ 3 4 ] Both children had concurrent vitiligo over which subsequently psoriasis and LP developed.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 While the former presents vesicles or blisters limited to preceding LP lesions, the latter is characterized by coincidence of LP lesions and LP-independent blistering lesions induced by an autoimmune mechanism against hemidesmosomal protein, such as BP180. 1,2 While the former presents vesicles or blisters limited to preceding LP lesions, the latter is characterized by coincidence of LP lesions and LP-independent blistering lesions induced by an autoimmune mechanism against hemidesmosomal protein, such as BP180.…”
mentioning
confidence: 99%
“…Dear Editor, Lichen planus (LP) is characterized by hyperkeratotic polygonal papules and plaques on skin surface and mucosae, and can be classified into several clinical subtypes including blistering variants, such as bullous LP (BLP) and LP pemphigoides (LPP). 1,2 While the former presents vesicles or blisters limited to preceding LP lesions, the latter is characterized by coincidence of LP lesions and LP-independent blistering lesions induced by an autoimmune mechanism against hemidesmosomal protein, such as BP180. Here, we report a case of BLP concomitant with elevation of serum anti-BP180 autoantibody.…”
mentioning
confidence: 99%
“…reported a case of bullous LP arising in the skin graft donor site of a psoriatic patient. [ 9 ] McGimpsey and O’Brien reported oral lichen planus with psoriasis. [ 10 ] Ujiie et al .…”
mentioning
confidence: 99%